(Im)politeness employed by multilingual Indonesian EFL learners in argumentative conversations - Emi Nursanti; Erna Andriyanti; Ikha Adhi Wijaya (Universitas Syiah Kuala, 2023)
Politeness might lessen imposition in argumentative conversations which potentially result in conflict. However, different conventions on politeness among different cultures may cause problems for EFL (English as a Foreign Language) learners who often transfer their native communication preferences to their target language usage. This article explores the (im)politeness employed by multilingual EFL learners in casual agreeing-disagreeing exchanges among peers. Using explanatory sequential mixed method design, students’ utterances in role plays were analyzed based on Leech’s (2014) politeness theory, Kakava’s (1993) disagreement strategies, as well as Locher’s (2004) mitigating strategies on disagreement. It is found that in conversations with people of equal status and power, the observance of politeness maxims is more apparent than the violation. It indicates that maintaining others’ faces is essential irrespective of age differences, even in arguing conversations. The more frequent use of positive politeness than negative politeness strategies represents their greater orientation to others than to themselves. The prevalence of mitigated disagreement and the frequent use of an appreciation preface also show their priority to maintaining good relationships. Those findings support the view of Asians as a collectivistic group whose primary concern in communication is group membership. This suggests that awareness of politeness in argumentative conversations among EFL learners must be increased by giving them different perspectives from non-Asian cultures.